新しい脊柱後彎の定量的測定方法の提案 - 植田 拓也; 柴 喜崇; 水野 公輔; 佐藤 春彦; 渡辺 修一郎 (理学療法学, 2014)
Purpose: This study aimed to examine the reproducibility and validity of a new quantitative method for measuring spinal kyphosis using a small gyro sensor. Method: Subjects were 96 community-dwelling middle-aged and elderly (mean age, 72.7 ± 6.2 years) people who performed a gymnastic exercise. We measured spinal kyphosis using 2 methods: (1) the kyphosis angle (KA) using a small gyro-embedded posture-measuring device and (2) the kyphosis index using a flexible ruler. We examined the reproducibility of the new method by obtaining 2-3 consecutive measurements and adequate number of measurements for KA. We also assessed the validity of KA measurement using the device. Statistical analysis: We used interclass correlation coefficients (ICCs) of KA reproducibility and a Pearson's product-moment correlation coefficient between KA and kyphosis index for determining the validity of KA measurement. Results: ICC (1,1): the reproducibility of repeated measurements was 0.967 (95% confidence interval [95% CI], 0.951-0.978) for 2 measurements and 0.956 (95% CI, 0.941-0.970) for 3 measurements, suggesting a high reproducibility for KA measurement using this method. The result of more than 0.95 for ICC (1,1) suggests that a single measurement of KA is sufficient. For the validity of KA measurement, a statistically significant correlation was shown between KA and kyphosis index. Conclusion: Thus, KA measurement using a small gyro-embedded posture-measuring device is highly reproducible in consecutive measurements as well as highly valid; this may be a useful quantitative method for measuring spinal kyphosis in the research or clinical environment. 【目的】本研究の目的は小型ジャイロセンサを用いた脊柱後彎変形(以下,円背)の定量的測定の再現性および妥当性を検討することである。【方法】参加者は神奈川県S市のラジオ体操会会員から募集した地域在住中高齢者96名(平均年齢72.7±6.2歳)とした。円背測定は小型ジャイロセンサ内蔵の姿勢測定装置(以下,姿勢測定装置)を使用した脊柱後彎角度(Kyphosis angle),外的基準として円背の程度をKyphosis indexにて算出した。姿勢測定装置による脊柱後彎角度測定の2回および3回連続測定の再現性,妥当性について検討した。【結果】Kyphosis angleの連続測定の再現性では,2回連続測定でICC(1,1):0.967(95% CI;0.951-0978),3回連続測定でICC(1,1):0.956(95% CI;0.941-0.970)となり,高い再現性が確認された。また,姿勢測定装置による脊柱後彎角度測定はKyphosis angleのICC(1,1)の結果から,1回測定で十分な再現性を得られることが確認された。また,Kyphosis angleとKyphosis indexの間には,全参加者(r=-0.63, p<0.01, n=96),男性(r=-0.64, p<0.01, n=50),女性(r=-0.62, p<0.01, n=46)において統計学的に有意な中等度の相関がみられ,Kyphosis angle測定の妥当性が確認された。【結論】姿勢測定装置による脊柱後彎角度測定は,再現性および妥当性が高く,臨床現場において簡便に実施可能な円背の定量的測定方法であることが示唆された。